Management of delusions of parasitosis: an interview with experts in psychodermatology - Nicholas Brownstone, MD; Josie Howard, MD; John Koo, MD (Wolters Kluwer, 2022)
Delusions of parasitosis (DOP), which is also called Morgellons disease or delusional infestation, can be one of the most challenging clinical encounters in a dermatologist's practice. One reason for this is lack of education during dermatology residency and a paucity of resources for the practicing dermatologist such as specialized psychodermatology clinics for these patients. To help close this knowledge gap, an interview was conducted with 3 experts in the field of psychodermatology and their responses were recorded and edited with goal of improving care for patients suffering from DOP by educating the busy, practicing dermatologist. The experts discussed many topics regarding DOP including the difference between primary and secondary DOP, how to build a good rapport with DOP patients, why the condition is seen mostly in older woman, and which medications are effective for treatment. The interview ends with a few high-yield practical treatment tips.